Conrad's Secrets - Hampson, R.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Conrad's Secrets explores a range of knowledges which would have been familiar to Conrad and his original readers. Drawing on research into trade, policing, sexual and financial scandals, changing theories of trauma and contemporary war-crimes, the book provides contexts for Conrad's fictions and produces original readings of his work.
Keywords: Literature .; Literature—Philosophy.; Culture—Study and teaching; Fiction; Literature, Modern—20th century; Literature, Modern—19th century; Postcolonial/World Literature; Literary Theory; Cultural Theory; Fiction; Twentieth-Century Literature; Nineteenth-Century Literature